Targeted delivery of curcumin and CM11 peptide against hepatocellular carcinoma cells based on binding affinity of PreS1-coated chitosan nanoparticles to SB3 protein - Danial Rahmani; Ramezan Ali Taheri; Mehrdad Moosazadeh Moghaddam (Amino Acids)
Abstract In recent years, the use of cationic peptides as alternative drugs with anticancer activity has received attention. In this study, the targeted release of curcumin (Cur) and CM11 peptide alone and together against hepatocellular carcinoma (HCC) was evaluated using chitosan nanoparticles (CS NPs) coated with Pres1 that target the SB3 antigen of HCC cells (PreS1-Cur-CM11-CS NPs). SB3 protein is the specific antigen of HCC and the PreS1 peptide is a part of the hepatitis B antigen, which can specifically bind to the SB3 protein. Chitosan was used to prepare NPs. To Cur and CM11 loading, drugs were added to the CS solution in appropriate concentrations. Pres1 was coupled to the surface of the NPs using EDC catalyst to target NPs against HepG2 cells. SEM and DLS analysis confirmed that the PreS1-Cur-CM11-CS NPs had a size of about 132 nm, the ideal size for penetrating the cell membrane. The loading of Cur and CM11 was equal to 87% and 65%, respectively, which had a sustained and better release in the acidic environment than in the physiological environment. The MTT assay showed that PreS1-Cur-CM11-CS NPs act in a targeted and specific manner with the highest toxicity on the HepG2 cells compared to the control by a decrease in viability of about 26% after 48 h based on cell apoptosis. The results showed that PreS1-Cur-CM11-CS NPs are capable of targeted and specific drug release against HepG2 cancer cells and have significant potential to fight this cancer. Graphical abstract